The Formation of Competitive Advantages for Corporate Structures Based on the Cluster Integration - Pustynnikova, Ekaterina Vasilyevna; Uskova, Elena Olegovna (Economy of Regions, 2017)
The article studies the cluster forms of integration as well as the development of corporate and cluster connections. At present, economic knowledge is rather focused on the development of integrated regional systems recognized as one of the most effective forms of integration. In turn, the processes, based on the interdependence and cooperation of economic entities located on the same territory, determine the possibility of stable economic relations, synergetic effect and growth of the competitive advantages of these territories. Such development tendencies reflect corporate interests and define trends for the integration of corporations in the context of regional and industrial limitations. Thus, one of the main aspects of integration is focused on the establishment of sustainable cost-beneficial relationships between corporate entities. The dialectical unity of the coordination and cooperation of corporate structures in economic clusters expands the traditional boundaries of economic benefits. Considering the government of corporate structure on the basis of internal approach, we can see that the benefits from the fragmented leadership may be neutralized due to unevenness of expenses. The corporate-cluster approach of corporate structure government allows not only to coordinate actions at the micro-level but also to generate more sustainable economic relations at the industrial, market and regional levels. It is reflected in the synergistic effect. The coordination of economic processes and geographic concentration contribute to system flexibility and adaptability in the market conditions as well as stimulate economic processes. Therefore, all cluster participants benefit from mutually beneficial cooperation. This, in turn, contributes to the decrease of total expenses and hastens the responses of entities on different market changes. The authors’ hypothesis assumes the coordination of interests in the economic cluster that allows to create grounds for economic growth and spread the tendency of sustainable development among all the parties of this interaction. This approach proves the feasibility of the formation of competitive advantages for corporate structures through cluster integration. The findings of this paper can serve as a methodological basis for the development and implementation of socio-economic programs in different regions. In the framework of current research, the algorithm of economic cluster formation was recommended for practical application to the Government of the Ulyanovsk region.